Information literacy and lifelong learning : policy issues, the workplace, health and public libraries - Crawford, John.; Irving, Christine (Burlington : Elsevier Science, 2013)
This book reviews the role of information literacy (IL) in developing employability skills, personal health management and informal learning from a variety of areas including: information policy issues, information usage and training needs and skills development. Early years education, lifelong learning and the role of IL in relevant organisations, including government departments, skills agencies, and professional bodies will also be considered. With a UK focus, this book also considers the leading role of the US in the development of information literacy policy.
Overview -- Specific areas -- Policymaking and issues for the future.
Print version record.
Keywords: Information literacy; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- Archives & Special Libraries; Information literacy; Electronic books; Electronic books